(De)Constructing Liberating Narratives: The Ideas and Logic behind the Translations of Dalit Autobiographies from Vernaculars to English (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The paper aims to discuss the opportunities that are hidden in the translation of Dalit literature into regional and major languages and answers three crucial research questions. Second, the paper discusses the role of translation as the means for changing the world and practices and as the means for building bridges between cultures and establishing solidarity. Discussing the examples of the works of Om Prakash Valmiki, Manoranjan Byapari, and Bama (Faustina Mary Fatima Rani), the paper explores how the translation of Dalit literature into major vernacular languages contextualizes the increase in the number of liberating narratives, making the narratives of the excluded people groups more visible within the mainstream literary corpus.